645. Absence of Toxemia in Clostridioides difficile infection: Results from Ultrasensitive Toxin Assay of Serum. (31st December 2020) - Sprague, Rebecca; Warny, Karolyne; Pollock, Nira; Daugherty, Kaitlyn; Lin, Qianyun; Xu, Hua; Cuddemi, Christine; Barrett, Caitlin; Banz, Alice; Lantz, Aude; Garey, Kevin W; Gonzales-Luna, Anne J; et al.
Abstract: Background: Clostridioides difficile infection (CDI) is the major cause of hospital-acquired bacterial infectious diarrheacaused by Toxin A (TcdA) and Toxin B (Tcd B), secreted from pathogenic strains of C.difficle bacteria. This infection can vary greatly in symptom severity and presentation. In fulminant CDI, these toxins lead to systemic complications such as toxemia, however, identification of toxemia in CDI patients is extremely rare. We hypothesized that this rarity of detection may be due to low concentrations of circulating toxins in the blood, below the limit of detection of commercially available assays. Methods: The previously developed Single Molecule Array (Simoa) assay, capable of detecting TcdA and TcdB in stool, was modified for the detection of toxins in serum and applied to a panel of serum samples from patients with confirmed CDI. Results: Our cohort included 169 patients with a median age of 68 years (IQR 54-78), most with severe CDI and many with severe clinical outcomes attributed to CDI (Table 1). We found no detectable TcdA or TcdB in the serum of our patient cohort despite a wide range of toxin concentrations in paired stool (Figure 1). The detection of toxin may be limited by the interference of anti-toxin anti-bodies circulating in serum. When serum samples were spiked with TcdA and/or TcdBvarying amounts of IgA, IgG or IgM anti-toxin, high serum anti-toxin antibody concentrations were associated with loss of Simoa signal, suggesting substantial inhibition of toxin measurements. Table 1. Demographics, Baseline Laboratory Values, and Clinical Outcomes for the cohort Figure 1. Comparison of TcdA and TcdB concentrations, as measured by Simoa, in serum and stool. Clinical cutoffs are shown: stool, 20 pg/ml for TcdA and for TcdB; serum 15.0 pg/ml for TcdA and is 26.7 pg/ml for TcdB. Signals below these cut-offs are below backgrounds and so negative. Conclusion: In contrast to earlier published findings which reported on the presence of detectable toxin in the serum of a small number of patients with CDI, our work did not support this observation. Although Simoa is highly sensitive for detection of picogram quantities of TcdA or TcdB it was unable to detect either toxin in serum during CDI. This result does not support the hypothesis that toxemia develops even in severe C. difficile infection. Disclosures: Alice Banz, Ph.D, BioMerieux (Employee) Kevin W. Garey, PharmD, MS, FASHP, Merck & Co. (Grant/Research Support, Scientific Research Study Investigator) Carolyn D. Alonso, MD, FIDSA, Alnylam Pharmaceuticals (Employee)Merck (Research Grant or Support) Ciarán Kelly, MD, Artugen (Consultant)Facile Therapeutics (Consultant)Finch (Consultant)First Light Biosciences (Consultant)Matrivax (Consultant)Merck (Consultant)Vedanta (Consultant)